Forecasting needs in the supply department using the ARIMA model in terms of economic security - Kozicki, Bartosz; Tomaszewski, Jarosław; Mizura, Grzegorz; Piotrowski, Andrzej (Nowoczesne systemy zarządzania, 2020)
W artykule wykonano przegląd literatury związanej z planowaniem, wydatkami, potrzebami, prognozowaniem i bezpieczeństwem ekonomicznym. Przeprowadzono analizę i ocenę szeregu czasowego wydatków poniesionych w dziale zaopatrzenia w podmiocie badań. Ocena pozwoliła na dobór modelu ARIMA do prognozowania wydatków (potrzeb) na przyszłość. Uzyskane prognozy zostały poddane analizie i ocenie. Opracowanie kończy się podsumowaniem i wnioskami. The article reviews the literature related to planning, expenses, needs, forecasting and economic security. An analysis and evaluation of the time series of expenses incurred in the procurement department in the subject of the study was performed. The assessment allowed for the selection of the ARIMA model to forecast expenses (needs) for the future. The obtained forecasts were analyzed and assessed. The study ends with a summary and conclusions.